PENGARUH DEBT TO EQUITY RATIO, GROWTH OPPORTUNITY DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2018-2022) - Widya Aprilya; Hesti Setiorini; Hernadianto Hernadianto; Yudi Partama Putra (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Growth Opportunity, and Dividend Policy on Firm Value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2022 period. The research method used is quantitative, utilizing secondary data obtained from the companies' annual financial reports. The study population consisted of 30 companies, and using a purposive sampling technique, 11 companies were sampled over a five-year observation period, resulting in 55 observations. Data analysis was performed using panel data regression with the help of EViews 12, and the best model selected was the Fixed Effect Model (FEM). The results indicate that partially, Debt to Equity Ratio (DER), Growth Opportunity, and Dividend Policy do not significantly influence Firm Value, with probability values ​​of 0.8090, 0.0762, and 0.6887, respectively, all greater than 0.05. However, the research model was simultaneously declared feasible with a Prob(F-statistic) value of 0.0000. The Adjusted R-Squared value of 0.675969 indicates that the Debt to Equity Ratio, Growth Opportunity, and Dividend Policy variables explain 67.59% of the variation in Firm Value, while the remaining 32.41% is explained by other variables outside the research model. The conclusion of this study indicates that Debt to Equity Ratio, Growth Opportunity, and Dividend Policy are not factors influencing Firm Value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2018–2022 period. Keywords: Debt to Equity Ratio, Growth Opportunity, Dividend Policy, Firm Value, Food and Beverage Companies